Influência da catálise ácida e básica na preparação da sílica funcionalizada pelo método sol-gel - Nassar, Eduardo José; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Sociedade Brasileira de Química, 2002)
Some aspects of the chemistry involved in the preparation and characterization of functionalized silicon oxide by sol-gel method are considered in this work. The synthesis was performed with different silicon alcoxide precursors and the influence of the acid and basic catalyst was investigated. Characterization was performed by infrared absorption spectroscopy, elemental analysis and 29Si NMR. Infrared data show Si-C and -CH2- vibrational modes at 1250 to 1280 and 2920 to 2940 cm-1, respectively. The elemental analysis confirmed the presence of organic groups in the inorganic silica network. 29Si NMR results show different hydrolisys depending on the acid or base catalysis.
Base and acid catalysis in the preparation of functionalized silica obtain by sol-gel method
Keywords: sol-gel; RMN 29Si and 13C; silica